Short‐term observations of double‐peaked Na emission from Mercury's exosphere - S. Massetti; V. Mangano; A. Milillo; A. Mura; S. Orsini; C. Plainaki (Geophysical Research Letters)
Abstract We report the analysis of short‐term ground‐based observations of the exospheric Na emission (D1 and D2 lines) from Mercury, which was characterized by two high‐latitude peaks confined near the magnetospheric cusp footprints. During a series of scheduled observations from the Télescope Héliographique pour l'Etude du Magnétisme et des Instabilités Solaires (THEMIS) telescope, achieved by scanning the whole planet, we implemented a series of extra measurements by recording the Na emission from a narrow north‐south strip only, centered above the two emission peaks. Our aim was to inspect the existence of short‐term variations, which were never analyzed before from ground‐based observations, and their possible correlation with interplanetary magnetic field variations. Though Mercury possesses a miniature magnetosphere, characterized by fast reconnection events that develop on a timescale of few minutes, ground‐based observations show that the exospheric Na emission pattern can be globally stable for a prolonged period (some days) and also exhibits fluctuations in the time range of tens of minutes.